Should antenatal corticosteroids be done after 34 weeks of gestation? Review article - (:unkn) unknown (My University, 2016)
0

Late preterm infants constitute the majority of preterm labors. The neonatal morbidity and mortality among late preterm infants are serious problems of obstetrical practice. This arises the question of antenatal corticosteroid administration beyond 34 week of gestation. In this review, need for antenatal corticosteroids after 34 weeks of gestation is studied.
Keywords: Diş Hekimliği; Farmakoloji ve Eczacılık; Toksikoloji